2003
DOI: 10.1002/ptr.1156
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of lethal effects of gamma rays in Swiss albino mice by Tinospora cordifolia

Abstract: Tinospora cordifolia is widely used in Ayurvedic medicines. It is known for its immunomodulatory, antihepatotoxic, antistress and antioxidant properties. It has been used in combination with other plant products to prepare a number of Ayurvedic preparations. The present study was undertaken to evaluate the radioprotective effect of an aqueous extract of Tinospora cordifolia (TC) against (60)Co gamma radiation. Oral administration of TC 5 mg/kg body wt to Swiss albino mice 1 h and 15 days prior to whole body ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…2B). Some earlier studies by like that of Pahadiya and Sharma (2003) have also reported the radioprotective properties of Tinospora.…”
mentioning
confidence: 82%
“…2B). Some earlier studies by like that of Pahadiya and Sharma (2003) have also reported the radioprotective properties of Tinospora.…”
mentioning
confidence: 82%
“…The methanol extract of Tinospora contains phenylpropanoids, norditerpene furan glycosides, diterpene furan glycosides and phytoecdysones [37]. The roots of T. cordifolia are also reported to contain other alkaloids like choline, tinosporin, columbin, isocolumbin, palmatine, tetrahydropalmatine and magnoflorine [38ā€“40]. …”
Section: Medicinal Plants and Cancermentioning
confidence: 99%
“…Palmatine enhance the antioxidant enzyme levels for antioxidant enzyme activity like GSH, SOD, catalase, and inhibited lipid peroxidation hence showing its role in detoxification pathway. Both enzyme activities and histological analysis suggest that environmental carcinogens that induce skin carcinogenesis can be inhibited by oral administration of palmatine in the daily diet to achieve protection against skin cancer and can inhibit papilloma growth [44] (Table 1). As an adjuvant therapy: Tinospora is effective for prevention of mucositis in patients with head and neck cancer receiving Radiotherapy [45].…”
Section: Tinospora Cordifolia (Guduci)mentioning
confidence: 99%